Love as Resistance: Exploring Conceptualizations of Decolonial Love in Settler States. Issue 3 (1st December 2019) - Moreno, Shantelle
Abstract : In this article, I weave together connections between notions of decoloniality and love while considering implications for decolonial praxis by racialized people settled on Indigenous lands. Through a community-based research project exploring land and body sovereignty in settler contexts, I engaged with Indigenous and racialized girls, young women, 2-Spirit, and queer-identified young adults to create artwork and land-based expressions of resistance, resurgence, and wellbeing focusing on decolonial love. Building on literature from Indigenous, decolonizing, feminist, and post-colonial studies, I unpack the ways in which decolonial love is constructed and engaged in by young Indigenous and racialized people as they navigate experiences of racism, sexism, cultural assimilation, and other intersecting forms of marginalization inherent in colonial rule. I uphold these diverse perspectives as integral components in developing more nuanced and situated understandings of the power of decolonial love in the everyday lives of Indigenous and racialized young peoples and communities.